ANALISIS PENGARUH KETIDAKSEIMBANGAN BEBAN TERHADAP EFISIENSI TRANSFORMATOR DISTRIBUSI 100 kVA PADA PT. PLN (PERSERO) UNIT AIMAS - john ohoiwutun; Markus Dwiyanto Tobi (Electro Luceat, 2019)
The increasing population development in Sorong district is seen from the mushrooming of developers who build housing and the construction of shops which of course the need for electrical energy continues to increase. Thus electricity is an important requirement in human life so as to obtain electricity reliably and continuously, PLN is required to manage to maintain a stable distribution of electrical energy that is sustainable to consumers. One phenomenon that is always experienced in the field is the uneven distribution of loads from the secondary side of the transformer to the customer. This causes unbalanced load between phase R, S and T which in turn causes the current to flow in the neutral conductor of the transformer, so that the current causes losses in the transformer. In this study an analysis was conducted to find out how much influence the load losses have on the efficiency of the 100 kVA distribution transformer at PLN. After calculating and analyzing, it is found that due to load imbalance in R, S and T phases, this results in daytime load losses of 0.499 kW and increases at night by 0.746 kW. Increasing load losses results in lower transformer performance and lower efficiency.